Acantholytic Pityriasis Rubra Pilaris Associated with Imiquimod 3.75% Application. (31st October 2011) - Atanaskova Mesinkovska, Natasha; Dawes, Danyelle; Sood, Apra; Bergfeld, Wilma
Abstract : Imiquimod is an immunomodulator with both antitumor and antiviral properties. It is currently available in two cream formulations as Aldara (imiquimod 5%) and the newly approved Zyclara (imiquimod 3.75%). Imiquimod has been associated with localized erythema, crusting, and scaling at the site of application. However, more severe generalized skin eruptions including erythema multiforme, psoriasis, and hyperpigmentation have been described. The newly approved imiquimod 3.75% cream is a presumably safer alternative due to its lower concentration. This paper describes the development of generalized acantholytic pityriasis rubra pilaris after the treatment of an actinic keratosis on the forehead with imiquimod 3.75% cream.